2018
DOI: 10.1021/jacs.8b06062
|View full text |Cite
|
Sign up to set email alerts
|

Near-Perfect CO2/CH4 Selectivity Achieved through Reversible Guest Templating in the Flexible Metal–Organic Framework Co(bdp)

Abstract: Metal–organic frameworks are among the most promising materials for industrial gas separations, including the removal of carbon dioxide from natural gas, although substantial improvements in adsorption selectivity are still sought. Herein, we use equilibrium adsorption experiments to demonstrate that the flexible metal–organic framework Co­(bdp) (bdp2– = 1,4-benzene­dipyrazolate) exhibits a large CO2 adsorption capacity and approaches complete exclusion of CH4 under 50:50 mixtures of the two gases, leading to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
139
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(144 citation statements)
references
References 55 publications
4
139
0
1
Order By: Relevance
“…The quest for switchable MOFs is driven to a large extent by a range of promising applications exemplified in reports on methane storage, molecular sensing, gas separation, proton conduction, and in reviews on drug delivery . Additionally, the studies of flexible MOFs are motivated by recently revealed novel counterintuitive phenomena such as negative gas adsorption or pronounced negative gas pressure .…”
Section: Introductionmentioning
confidence: 99%
“…The quest for switchable MOFs is driven to a large extent by a range of promising applications exemplified in reports on methane storage, molecular sensing, gas separation, proton conduction, and in reviews on drug delivery . Additionally, the studies of flexible MOFs are motivated by recently revealed novel counterintuitive phenomena such as negative gas adsorption or pronounced negative gas pressure .…”
Section: Introductionmentioning
confidence: 99%
“…The quest for switchable MOFs is driven to a large extent by a range of promising applications exemplified in reports on methane storage, molecular sensing, gas separation, proton conduction, and in reviews on drug delivery . Additionally, the studies of flexible MOFs are motivated by recently revealed novel counterintuitive phenomena such as negative gas adsorption or pronounced negative gas pressure .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the metal–organic frameworks (MOFs) material, with high specific surface area, tunable and large pore size, and diversity open metal sites, are showing great application potential of gas separation, sensing, energy storage and catalysis . Especially in the field of hydrogen storage, these properties facilitate the adsorption of H 2 on the surface of it.…”
Section: Introductionmentioning
confidence: 99%